Jocquestus, a new genus of trachelid sac spiders from the Afrotropical Region (Arachnida: Araneae) - Lyle, Robin; Haddad, Charles R. (Zootaxa, 2018)
The new dark sac spider genus Jocquestus gen. nov. (Araneae: Trachelidae) is proposed for two species of Afrotropical trachelid spiders, J. schenkeli (Lessert, 1923) comb. nov. (type species) from D.R. Congo, South Africa, Mozambique and Zimbabwe, and J. roeweri (Lawrence, 1938) comb. nov. from South Africa, both of which are transferred from Trachelas L. Koch, 1872. Both species are redescribed and the male of J. roeweri comb. nov. is described for the first time. Five new species are described: J. capensis sp. nov. (♂ ♀), J. harrisi sp. nov. (♀) and J. incurvus sp. nov. (♂ ♀) from South Africa, and J. griswoldi sp. nov. (♂) and J. obliquus sp. nov. (♂ ♀) from Tanzania. Present data suggests that all of the species are arboreal spiders associated with the vegetation of woody plants in savanna, forest and fynbos habitats, and are only very rarely encountered near the soil surface.